2003
DOI: 10.1088/0954-3899/29/10/305
|View full text |Cite
|
Sign up to set email alerts
|

Consistent application of the finite-range liquid-drop model to Langevin fission dynamics of hot rotating nuclei

Abstract: A generalized finite-range liquid-drop model based on the Yukawa-plusexponential potential was applied to describe fission dynamics of hot rotating nuclei. The potential energy, level-density parameter and Helmholtz free energy are calculated in a consistent way by using the generalized finiterange liquid-drop model. The level-density parameter was approximated by a leptodermous-type expression. The coefficients of this expansion are in surprisingly good agreement with those obtained earlier by Ignatyuk and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 43 publications
1
35
1
Order By: Relevance
“…The temperature of the heat bath T has been determined by the Fermi-gas formula T = (E int /a(q)) 1/2 , where E int is the internal excitation energy of the nucleus and a(q) is the level-density parameter, which has been taken from the work of Ignatyuk et al [16]. It should be noted that the asymptotic level-density parameter obtained by Ignatyuk and his co-workers is in surprisingly good agreement with the level-density parameter, calculated [17] in a consistent way by using a temperature-dependent finite-range liquid drop model [18]. The repeated indices in the equation above imply summation over the collective coordinates from 1 to 3.…”
Section: Multidimensional Langevin Equationsmentioning
confidence: 58%
“…The temperature of the heat bath T has been determined by the Fermi-gas formula T = (E int /a(q)) 1/2 , where E int is the internal excitation energy of the nucleus and a(q) is the level-density parameter, which has been taken from the work of Ignatyuk et al [16]. It should be noted that the asymptotic level-density parameter obtained by Ignatyuk and his co-workers is in surprisingly good agreement with the level-density parameter, calculated [17] in a consistent way by using a temperature-dependent finite-range liquid drop model [18]. The repeated indices in the equation above imply summation over the collective coordinates from 1 to 3.…”
Section: Multidimensional Langevin Equationsmentioning
confidence: 58%
“…The use of the Kramers factor allows one to match the fission rate (width) calculated by Eq. (20) and the quasistationary fission rate obtained in dynamical calculations (see, e.g., [26][27][28]). The appearance of the temperature in the denominator of Eq.…”
Section: Decay Of Excited Sh Nucleus and Its Survival Probabilitymentioning
confidence: 99%
“…Energy, angular and mass distributions of primary reaction fragments are given by formula (28) and Eqs. (25).…”
Section: Formation Of Superheavy Nuclei In Multinucleon Transfer Reacmentioning
confidence: 99%
“…The deformation dependence of the level-density parameter has been discussed in references [33,34,36,35]. In our case, the ratio a f /a n is calculated considering volume and surface dependencies as proposed in reference [36] .…”
Section: Dynamical Description Of Fission By the Abrabla Codementioning
confidence: 99%
“…[37]. A recent work of Karpov et al [35] has shown that equation (44) is well adapted by comparing it to several derivations: in the framework of the liquid-drop model including a Coulomb term [38], with the finite-range liquid-drop model [39] and within the relativistic mean-field theory [40]. The angularmomentum-dependent fission barriers are taken from the finite-range liquid-drop model predictions of Sierk [41].…”
Section: Dynamical Description Of Fission By the Abrabla Codementioning
confidence: 99%